Perancangan Media Pembelajaran Berbasis Kuis Interaktif pada Tingkat Sekolah Dasar Menggunakan Macromedia Flash 8 - Ali Ikhwan; Fairuz Azzaria Siregar; Najahaura Rahma; Nur Zahra Maharani (GLOBAL SCIENTS PUBLISHER, 2026)
Advancements in information technology have encouraged the emergence of various innovations in the field of education, one of which is the use of interactive learning media. However, the teaching and learning process in elementary schools still largely relies on conventional methods that tend to be less engaging for students. This study aims to develop an interactive quiz-based learning media using Macromedia Flash 8 to create a more attractive and effective learning experience. The development method employed is the Multimedia Development Life Cycle (MDLC), which consists of six stages: concept, design, material collecting, assembly, testing, and distribution. The developed media includes an introductory page, user identity input, multiple-choice questions, a timer, sound effects, background music, automatic score calculation, and an evaluation result page. The results indicate that the application is capable of providing interactive learning evaluation, is easy to use, and offers immediate feedback, thereby having the potential to enhance students' learning motivation.